Summer Classes in Higher Education: A Qualitative Study of Lecturer and Student Views - Bang, Truong Cong (VNU Journal of Science: Education Research; Vol 40 No 3DO - 10.25073/2588-1159/vnuer.4765, 2024)
Summer classes have become increasingly prevalent in higher education institutions worldwide, offering students opportunities to accelerate their learning, reduce course loads, and maintain academic momentum. This qualitative study explores the perspectives of lecturers and undergraduate students on the benefits, drawbacks, and strategies for success of summer classes. Semi-structured interviews were conducted with ten students and two lecturers from a university in Ho Chi Minh City, Vietnam. The findings reveal that the primary perceived benefits of summer classes include the ability to complete courses more quickly, have a lighter subject load during the regular year, and improve academic performance. However, the drawbacks cited were the sacrifice of leisure time or income from part-time work and the added pressure of condensed timelines. Recommended strategies comprise proactive promotion of summer class advantages to increase student awareness, careful selection and compensation of skilled instructors, and incorporation of recreational activities to support student well-being. This study contributes qualitative insights to inform the development of effective, student-centered summer programs in higher education.